Descriptive Profile of Anaphylactic Reaction Patients Hospitalized at RSUP Prof. DR. I.G.N.G Ngoerah Period 2018-2023 - Wijaya, Gede Bagus Rawida; Suardamana, I Ketut (Jurnal Indonesia Sosial Sains, 2024)
Introduction: Anaphylactic reaction is a severe, potentially life-threatening systemic hypersensitivity reaction caused by a specific allergen. This study aimed to evaluate the clinical profile of anaphylactic patients hospitalized in Prof. Dr. I.G.N.G. Ngoerah Hospital, Denpasar. Method: This was a cross-sectional descriptive study of anaphylactic patients hospitalized in our center from January 2018 to December 2023. Patients diagnosed with anaphylactic reactions were included in this study. All the data (demographic, clinical manifestations, potential trigger) were attained from medical records for descriptive analysis. Result: 292 patients were enrolled in this study; half were women (54,4%), and the median age was 38,50 years (interquartile range 24). The most common potential triggers were drugs (57%), followed by food (18,5%), blood products (14,1), insect bites, and other triggers (4,8%). Almost all patients experience skin and mucosal manifestations (99%). Anaphylactic shock occurs in only 22% of patients. Discussion: Previous studies have found similar results to our findings, and anaphylactic reaction caused by drugs was associated with a more severe reaction. The effect of estrogen hormones on more severe reactions has been reported in female mice, but human research is still limited. Conclusion: Further studies are needed to investigate the correlation between demographic characteristics or specific clinical manifestations with a severe reaction.